Self-Speaking Challenge Strategy Through Social Media in Enhancing Mahārah Al-Kalām - Adittia Batalipu; Ahmad Sayudi M. Zen; Damhuri; Muaz Al Iksan; Ratni Bt Hj Bahri (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the role of the social media-based self-speaking challenge in improving the Arabic speaking skills (mahārah al-kalām) of Arabic Language Education students. The background of this research lies in the fact that speaking is often the most challenging skill, due to both limited vocabulary and low self-confidence. This research employed a descriptive qualitative approach with data collected through video observation, comment analysis, and in-depth interviews. The findings reveal that the self-speaking challenge enhanced students’ fluency, vocabulary variation, and sentence structure mastery. Furthermore, the strategy significantly fostered self-confidence and reduced students’ anxiety or shyness in speaking Arabic in digital public spaces. Audience comments functioned both as motivational support and as peer linguistic feedback that strengthened the learning process. The novelty of this study lies in its identification of the dual function of audience comments as both affective support and linguistic peer feedback, a dimension that has received limited attention in previous studies on social media-based Arabic language learning. The study concludes that social media can serve as a dynamic pedagogical space, rather than merely an entertainment platform, with significant contributions to the development of Arabic speaking skills.